Unpacking The Lived Experiences of Gendered Violence Against Queer Individuals and Its Impact on Their Daily Lives in Ncise Village, Eastern Cape, South Africa - Gawuzela, Abongile; Kasa, Luvo (Journal of Ecohumanism, 2025)
This study explores the experiences of gendered violence against Queer individuals shedding light on the intersectional forms of discrimination and violence that they encounter. Queer individuals experience high rates of gendered violence across the globe that is caused by societal norms, legal discrimination, and cultural shame. This qualitative study was conducted in Ncise village, Eastern Cape, South Africa, using the phenomenological design and collected data from 20 participants through in-depth and semi-structured interviews. The study sought to explore how institutional structures, power relationships, and societal norms support and perpetuate violence against Queer individuals. Underpinned by the Anti-Oppressive Practice (AOP) and cultural Competence as theoretical frameworks, the study sought to transform social attitudes and values as well as influence social work practices and to develop the skills and knowledge necessary to engage with diverse cultural groups, including Queer individuals effectively. This study advocates for the development of social work policies that will safeguard Queer individuals from gendered violence and to spearhead educational initiatives that raise awareness about hate crimes. Ultimately, the study brings advanced knowledge on the complex and multifaceted nature of gendered violence against Queer people, which will guide the development of more effective interventions, legislation and support systems.